Analisis Fenomena Anak Sebagai Pelaku Kejahatan Penipuan Online di Kabupaten Wajo dari Perspektif Kriminologis - Muharawati; Hardian Kumala; Ramadhani, Wulan Suci; Nurfadillah; Yuswan, Muhammad; Sunarti; Alfarizy, Azhar (Legal Journal of Law, 2024)
This study aims to determine the prevention efforts for children as perpetrators of online fraud, as well as to determine the factors that cause children to commit online fraud. This study was conducted at the Wajo Police and Class II B Sengkang Detention Center with data collection methods through documentation and interviews. The data and information obtained by the author were analyzed qualitatively, then analyzed descriptively in order to obtain answers to the problems studied by the author. Based on the results of the study, it can be concluded that the factors that cause children to commit online fraud in Wajo Regency are the fun or trial factor, the follower factor, economic factors, environmental factors, educational factors, and the minimal factor of being caught by the authorities. In addition, various prevention efforts carried out by the Wajo Police range from pre-emptive, preventive and repressive efforts.